1982
DOI: 10.3133/ofr83272
|View full text |Cite
|
Sign up to set email alerts
|

The weathering of brick; causes, assessment and measurement

Abstract: The composition and processing of raw materials can effect both short-and long-term alteration. On exposure to moisture, brick raw materials rich in sodium and potassium expand more than materials rich in calcium, alumina, and magnesium. Mineral grains such as calcite, dolomite, pyrite, and siderite are associated with cracks, spalls, and pops in bricks, and some lime-rich Pleistocene materials develop complete friability unless treated with steam or water during cooling. Bricks made from illite-rich raw mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1986
1986
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…The Winkler compendium includes contributions from seventeen recognized authors covering topics such as stone properties, stone weathering, and stone preservation; the treatment also includes comprehensive literature reviews in all of these areas. Another extensive literature review, specialized in the area of brick weathering, has been released by Hughes and Bargh (1982).…”
Section: Historical Reviewmentioning
confidence: 99%
“…The Winkler compendium includes contributions from seventeen recognized authors covering topics such as stone properties, stone weathering, and stone preservation; the treatment also includes comprehensive literature reviews in all of these areas. Another extensive literature review, specialized in the area of brick weathering, has been released by Hughes and Bargh (1982).…”
Section: Historical Reviewmentioning
confidence: 99%
“…Ceramic materials, like fired brick, often deteriorate due to their ability to retain moisture. A wet environment grows mold and organic material, which weakens the brick (Hughes, Bargh 1982) . This mold is a detriment to the building's lifespan and inhabitants' health (EPA 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Efforts to find better raw materials and improve the manufacture of fired-clay products have taken place over the last six decades at the Survey. Relevant parts of these efforts are summarized in Hughes and Bargh (1982), Hughes (1983), White (1983), andHughes (1993). Slonaker (1977) showed that acceptable bricks were produced from feeds of 72% fly ash, 25% bottom ash, and 3% sodium silicate.…”
Section: Introductionmentioning
confidence: 99%